Pola Gender dalam Peternakan Babi Pada Peternak Etnis Arfak, Papua Barat - Deny A. Iyai; Desni T.R. Saragih (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2015)
The aim of this research was study of women and man concerning on pig family farming on Arfak ethnic, West Papua. Descriptive study was done in agro-ecological zones, i.e. coastal, lowland and highland. A 22 pig farmers were involved and interviewed subsequently, 10 hh, 7 hh and 5 hh. The finding of this research was that pig production level of the women was smaller than man in pre-production. Although increases in production level till pasca production. Man pig farmers were still dominant keeping the animals. However, decision was done democraticly. Level of income kept by women and men were in the ranges of Rp 2 million to Rp 6 million. Keywords: gender, livestock agro-ecology, pre-production, production, pasca-production, Arfak.